Trend Analysis of the Increase of Air Temperature and and the Rainfall on Climate Change in Maros District - Sitti Nurhayati Hamzah; Muhammad Arsyad; Pariabti Palloan (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2024)
Research has been carried out which aims to analyze and gain knowledge about climate change that is happening in Maros Regency using descriptive, spatial and explanatory statistical methods. The data used is daily climatic data for Maros Regency which is processed using Ecxel, RCLIMDEX and ArcGIS 10.4 software which produces data in the form of graphics and spatial images. In addition, global factors are used as supporting data to determine its relationship with the climate of Maros Regency, to see whether climate change is occurring or only being influenced by global factors such as monsoons and El Nino/La Nina. The pattern of rainfall in Maros Regency is monsoonal, there has been no change in climate patterns for 30 years and there has been a decreasing rate of rainfall, but there has been an increase in the amount of rainfall at the peak of the rainy season and a decrease in rainfall at the peak of the dry season every tenth of the year and the extreme index has increased. The air temperature in Maros district is also experiencing an increasing trend, although it is more significant at the minimum temperature.